Fishery and some aspects of the biology and ecology of the Sergestid shrimp, Acetes (Order Decapoda, Family Sergestidae) in Miagao, Iloilo, Philippines - Gaudiel, Rother M (2023.)
This study investigated the fishery and some aspects of the biology and ecology of the sergistid shrimp, Acetes, in Barangay Damilisan, Miagao, Iloilo, Philippinez using fishery dependent-data, formal interviews, sample collection, an analyses using FiSAT II software. Based on morphometric evaluation, the sergestid shrimps present in the study site were identified as Acetes intermedius. These minute-sized shrimps are known to aggregate in coastal waters during nighttime and are captured using beach seines. In Miagao, there were 28 licensed beach seine operators. The total line length of a beach seine towing line ranged from 130 to 280 m and was deployed at depths of 5 to 60 m. The operators were all males, and most of whom work under an owner, and earned 516.67 to 2,673.33 Php/week. The operations were affected by environmental factors like monsoons, tides, open and closed season, and time. In Brgy. Damilisan, the highest monthly mean catch rate was 90.33 kg/haul/ and the highest monthly estimated total landings were 2800.33 kg which was recorded in January 2022. mature and near-spawning specimens were >50% in January 2022, February 2022, and April 2022. size at sexual maturity was recorded at lengths ranging from 21.90 to 23.10 mm. The male-to-female sex ratio was 1:2 ; wherein females dominated the males. The highest frequency for females ranged from 20.50-22.40 mm (TL). Estimated population parameters of A. intermedius were L∞ = 30.98 mm, K = 1.900 yr-1, ⊘" = 3.26 yr-1, tmax = 1.6 yr-1, M = 3.93 yr-1, F = 4.07 yr-1, Z =8.00 yr-1, E = 0.51, E₀.₁ = 0.517, E₀.₅ = 0.349, Emax = 0.691, L50%/Lc = 13.45 mm, and L75% = 14.57 mm with a unimodal type of recruitment pattern. The value obtained for the exploitation rate was above 0.5, suggesting the Acetes stocks in Brgy. Damilisan faced over exploitation. These results provide information that canbe used to properly conserve, utilize, and manage the Acetes fishery industry in Miagao, Iloilo, Philippines.
Thesis (M.S. Fisheries - Fisheries Biology) -- Miagao, Iloilo : University of the Philippines Visayas, March 2023.